# sol4 - SOLUTIONS FOR HOMEWORK 4 3.1.5. (b) Pick ε > 0,...

This preview shows page 1. Sign up to view the full content.

This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: SOLUTIONS FOR HOMEWORK 4 3.1.5. (b) Pick ε > 0, and show that there exists N ∈ N s.t. |2n/(n + 1) − 2| < ε for n > N . A simple calculation shows that |2n/(n + 1) − 2| = 2/(n + 1). We know that there exists N ∈ N s.t. 1/N < ε/2. Then |2n/(n + 1) − 2| < ε for n > N . 3.1.10. Let ε = x/2. Then there exists M ∈ N s.t. |x − xn | > ε for any n > M . By the triangle inequality, for such n x x xn ≥ x − |x − xn | > x − = > 0. 2 2 3.1.14. We show that lim(2n)1/n = 1. Clearly, (2n)1/n > 1. Fix ε > 0, and show that (2n)1/n < 1 + ε for n > N (N ∈ N depends on ε). Indeed, (2n)1/n < 1 + ε iﬀ n 2n < (1 + ε)n = k =0 2 nk ε. k Find N ∈ N s.t. N > 4/ε + 1, or in other words, 2N < N (N − 1)ε2 /2. Then, for any n > N , n2 ε < (1 + ε)n , 2n < 2 as desired. 3.1.16. For n ≥ 3, hence, for such n, n! = 1 · 2 · 3 · 4 . . . · n ≥ 1 · 2 · 3 · 3 . . . · 3 = 2 · 3n−2 , 2n 2 ≤2 n! 3 n−2 = (here, we use the techniques of Example (b), p. 58 of the textbook). For any ε > 0 ﬁnd N ∈ N s.t. N ≥ 3, and 1/N < ε/4. Then 0 < 2n /n! < ε for any n > N . 3.2.7. In Theorem 3.2.3, both sequences are assumed to converge, which need not happen in our case. Thus, that theorem is inapplicable here. Find A > 0 s.t. |bn | < A for any n. Fix ε > 0, and show that there exists N ∈ N s.t. |an bn | < ε for any n > N . There exists N ∈ N s.t. |an | < ε/M for n > N . For such n, |an bn | < ε, and we are done. 3.2.9. Multiplying by the “conjugate,” we get: √ √ √ √ 1 n+1+ n yn = ( n + 1 − n) · √ √ =√ √, n+1+ n n+1+ n √ hence 0 < yn < 1/(2 n). For any ε > 0, ﬁnd N ∈ N s.t. 1/N < 4ε2 . Then |yn | < ε for any n > N , hence limn yn = 0. 1 2 2 4 < = n (1 + 1/2) n · 1/2 n 2 SOLUTIONS FOR HOMEWORK 4 √ ′ ′ Let yn = nyn , and xn = 1/yn = 1+ 1 + 1/n. By Theorem 3.2.10, lim 1 + 1/n = ′ 1. Therefore, by Theorem 3.2.3, lim xn = 2, and furthermore, lim yn = 1/ lim xn = 1/2. 3.2.12. Let xn = = But lim (1 + a/n)(1 + b/n) = lim(1 + a/n)(1 + b/n) = 1, hence lim (1 + a/n)(1 + b/n) + 1 = 2. Furthermore, lim(a + b + ab/n) = a + b, thus lim xn = (a + b)/2. 3.2.16. (a) Let xn = 1 for each n. Then xn+1 /xn = 1 for each n, and lim xn = 1. (b) Let xn = n. Then xn+1 /xn = 1 for each n, and the sequence (xn ) is unbounded, hence divergent. 3.2.18. (d) lim(n!/nn ) = 0. To establish this, let k = ⌊n/2⌋, and note that 0≤ (n + a)(n + b) − n = ( n(a + b) + ab n (1 + a/n)(1 + b/n) + n (n + a)(n + b) − n) · = a + b + ab/n (1 + a/n)(1 + b/n) + 1 (n + a)(n + b) + n (n + a)(n + b) + n . 1 · . . . · k (k + 1) · . . . · n kk n! n = · ≤ ≤ 2−k ≤ 21−n/2 = 2 2−1/2 . n k n−k n n n n −1/2 n By Example 3.1.11(b), lim(2 ) = 0, hence, by Squeeze Theorem, lim(n!/nn ) = 0. 3.2.19. Fix r ∈ (L, 1), and set ε = r − L. Then |xn − L| < ε for n > N , hence 1/n xn < L + ε = r . Therefore, 0 ≤ xn ≤ r n . An application of Squeeze Theorem and Example 3.1.11(b) shows that lim xn = 0. 3.3.2. We know that x1 > 1, and xn+1 = 2 − 1/xn . We use induction to show that this sequence is decreasing. More precisely, we show hat 1 < xn+1 < xn for every n. To this end, it suﬃces to establish the following: if a > 1, then 1 < 2 − 1/a < a. The left hand side inequality is obvious, and the right hand side is equivalent to 1 < (a + 1/a)/2. However, 1 ≤ (a + 1/a)/2 by the Arithmetic-Geometric Mean Inequality. Moreover, the equality holds iﬀ a = 1/a, which is not the case for us. Hence, 2 − 1/a < a. 3.3.4. Assume for a moment that the sequence (xn ) has a limit, call it x. Then √ √ x = lim xn+1 = lim 2 + xn = 2 + x, hence (solving the equation x2 = 2 + x) x = 2. We shall prove that, for each n, xn√ xn+1 < 2. To this end, it suﬃes to establish the < following: if 0 < √ < 2, then a < a + 2 < 2. √ a However, a + 2 > a + a = 2a > a · a, √ √ hence a + 2 > a2 = a. On the other hand, 2 + a < 2 + 2 = 2. Thus, the sequence (xn ) is increasing, and bounded by 2 from above. As we have already seen, lim xn = 2. 1/n SOLUTIONS FOR HOMEWORK 4 3 3.3.11. Note that the sequence (yn ) is increasing. Indeed, 1 1 1 1 + − = > 0. yn+1 − yn = 2n + 1 2n + 2 n + 1 (2n + 1)(2n + 2) On the other hand, yn is a sum of n terms, each less than 1/n, hence yn < 1 for each n. Therefore, the sequence (yn ) is increasing, and bounded above. Therefore, it converges. Back to: the syllabus, the main page of the course, the assignment. ...
View Full Document

## This note was uploaded on 09/30/2009 for the course MATH 444 taught by Professor Junge during the Spring '08 term at University of Illinois at Urbana–Champaign.

Ask a homework question - tutors are online